Recuperação e purificação de ramnolipídeos produzidos por pseudomonas aeruginosa P029-GVIIA utilizando melaço de cana como substrato - Oliveira, Ana Carmen dos Santos Mendes de (2010)
Biosurfactants are molecules produced by microorganisms mainly bacteria as Pseudomonas and Bacillus. Among the biosurfactants, rhamnolipids play an important role due to their tensoactive as well as emulsifying properties. Besides can be produced in a well consolidated way the production costs of biosurfactants are quite expansive mainly if downstream processing is goning to be considered. Actually, attention has been given to identification of biosurfactants as well as optimization of its fermentative processes including downstream ones. This work deals with the development of strategies to recovery and purification of rhamnolipids produced by Pseudomonas aeruginosa P029-GVIIA using sugar-cane molasses as substrate. Broth free of cells was used in order to investigate the best strategies to recovery and purification produced by this system. Between the studied acids (HCl and H2SO4) for the acid precipitation step, HCl was the best one as has been showed by the experimental design 24. Extraction has been carried out using petroleum ether and quantification has been done using the thioglycolic acid method. Adsorption studies were carried out with activated carbon in a batch mode using a 24 experimental design as well as combined with an hydrophobic resin Streamline Phenyl aiming to separate the produced biosurfactant. Biosurfactant partial identification was carried out using High Performance Liquid Chromatography (HPLC). Experiments in batch mode showed that adsorption has been controlled mainly by pH and temperature. It was observed a reduction of 41.4% for the liquid phase and the solid phase it was possible to adsorb up to 15 mg of rhamnolipd/g of activated carbon. The kinetics of adsorption has been well fitted to a pseudo-first order reaction with velocity constant (k1) of 1.93 x 10-2 min-1. Experiments in packed bed ranging concentration on eluent (acetone) has been shown the highest recovery factor of 98% when pure acetone has been used. The combined effect if using activated carbon with an hydrophobic resin Streamline Phenyl has been shown successful for the rhamnolipids purification. It has been possible to purify a fraction of the crude broth with 98% of purity when the eluted of activated carbon packed bed was used with pure acetone